Utilization of Learning Facilities and Infrastructure in Implementing the Merdeka Curriculum at Muhammadiyah Middle School 57 Medan - Anggraini, Sri Veronica; Muti'ah, Siti; Panjaitan, Riski; Setiawan, Muhammmad Raihan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Educational facilities really determine the success of education, because facilities and infrastructure play a very important role in the learning process. Facilities and infrastructure influence the learning process, thereby determining whether learning runs effectively and efficiently.The aim of this research is a way to identify and obtain discussion regarding the use of learning facilities and infrastructure in implementing the independent curriculum at Muhammadiyah 57 Medan SMP school. The method used in this research is a descriptive qualitative method, namely describing the subject about the situation and data obtained during this observation and research, namely the school principal, teachers and school committee. Data collection techniques use observation, interviews and documentation. This research states and provides an overview of the use of facilities and infrastructure in implementing the independent curriculum at Muhammadiyah 57 Medan SMP school. The results of this research prove that the implementation of the curriculum at SMP Muhammadiyah 57 Medan has been implemented optimally and is ongoing, although the implementation still has shortcomings and obstacles. The key to success comes from implementing the curriculum at Muhammadiyah 57 Medan SMP school, meaning that the principal and teachers must have the will to make changes. The principal as a leader must be able to change the mindset of the human resources in the school to want to make changes so that the independent curriculum can be implemented.